Speech Style in the lyric of Banyuwangi Folk Songs - Imam Suyitno (Humaniora, 2012)
Banyuwangi folksongs are the cultural product of the Using ethnic community. They are the results of the interaction between the Using people and their natural and socio-cultural surroundings. As cultural products, the folksongs contain utterances having distinct characteristics, which, from a theoretical point of view, are cultural expression of the Using people. These utterances have a variety of speech styles reflecting the diversity of communication strategies of Using people. These various speech styles serve to unite ideas and make them coherent, to articulate and emphasize the meaning of the utterances, and to develop the characteristics of the utterances. In the Using language, the use of these various speech styles reflect the social dynamics of the Using people in expressing politeness in their speech.